A critical role for non-coding RNA GAS5 in growth arrest and rapamycin inhibition in human T-lymphocytes. (22nd March 2011) - Williams, Gwyn T.; Mourtada-Maarabouni, Mirna; Farzaneh, Farzin
Abstract : Non-coding RNA GAS5 (growth arrest-specific transcript 5) is a 5′-TOP (5′-terminal oligopyrimidine tract) RNA, whose translation, and consequently also stability, is controlled by the mTOR (mammalian target of rapamycin) pathway. GAS5 was identified by functional expression cloning and is necessary and sufficient for normal growth arrest in both leukaemic and untransformed human T-lymphocytes. GAS5 is also required for the inhibitory effects of rapamycin and its analogues on T-cells. The striking functional effects of GAS5 may be mediated through the snoRNAs (small nucleolar RNAs) encoded in its introns and/or through the unusual folding of the mRNA itself, which sequesters, and therefore inhibits, the glucocorticoid receptor.